Stable expression and purification of Juvenile Hormone Binding Protein from Drosophila melanogaster Schneider line-2 cells - Tan, Si Hui (My University, 2007)
Studies on the hemolymph Juvenile Hormone Binding Protein (hJHBP) and Juvenile Hormone (JH) interaction have been considerably limited by the availability of pure hJHBP. An expression vector was created by cloning the recombinant JHBP (rJHBP) gene into pMT/BiP/V5-HisB vector and stably transfecting it into Drosophila melanogaster Schneider line-2 cells. The cells can be induced by copper sulfate to produce large quantities of rJHBP that is secreted into the medium. The rJHBP can be purified by passing it through a His-Tag column. Subsequent treatment with recombinant Enterokinase yields a protein that is similar to hJHBP in size. Results from radioactive binding assay affirm the functionality of rJHBP because it is able to bind JH rather efficiently. These suggest that rJHBP is folded and glycosylated in a manner similar to that of native hJHBP in Manduca sexta. This is the first successful instance of inducible expression of rJHBP in vitro.
21 p.
Keywords: Biochemistry; Entomology